Proposal of blended learning to improve the first mathematics courses at the University. The situation of the Universidad Nacional - Morales-López, Yuri (2014)
The General Mathematics course code MAX084 is designed to strengthen basic skills in mathematics precollege and thus ensure that students have the requirements for a calculus course. But the results obtained since 2007 reveal certain weaknesses and difficulties of students. Among the many factors involved are the small amount of time in which is told in the sessions to provide more relevant examples, time to strengthen high school knowledge and the amount of exercise to review. This proposal creates an input for the improvement of the activity in the General Mathematics MAX084 course taught by the Escuela de Matemática de la Universidad Nacional de Costa Rica (UNA) to different careers and colleges. The goal is a proposal to transform the traditional setting of MAX084 General Mathematics course by incorporating the virtual in teaching practices with the use of the Moodle platform. This is an evolution of the current processes of existing academic work at UNA, the tools available and a cultural change throughout the process.